Meningkatkan Aktivitas Dan Hasil Belajar Menggunakan Model Problem Based Learning Dikombinasikan Numbered Head Together Di Kelas 5 Sekolah Dasar - Ratu Januari Jala Sukma; Mahmuddin (CV. ITTC INDONESIA, 2023)
The issue in this study is the low action and understudy learning results. Endeavors to beat this by utilizing the Problem Based Learning up learning model joined with Numbered Head Together. The reason for this exploration is to portray instructor exercises, depict understudy exercises and investigate understudy learning results. This review utilized a subjective methodology and a Homeroom Activity Exploration (PTK) type with a plan of 2 patterns of 3 gatherings. The setting of this exploration was done in class 5 at SDN Kuin Cerucuk 4 Banjarmasin with a sum of 30 understudies. The kind of examination information is subjective and quantitative information. Information examination in this study utilized unmistakable investigation methods and cross-arrangements converted into tables, charts and understandings with rates. The outcomes showed that educator movement in cycle I meeting 1 by getting a score of 17 with great rules, in cycle II gathering 1 became 23 with excellent models. Understudy action in cycle I meeting 1 got a score of 63.33% with very dynamic models, in cycle II gathering 1 got a score of 100 percent with extremely dynamic measures. The old style fulfillment of understudy learning results in cycle I meeting 1 arrived at 40.00%, expanded in cycle II gathering 1 coming to 100 percent.